Preventing lower limb injuries in soccer players - Gioftsidou, A. F.; Malliou, P. K. (Strength and Conditioning Journal, 2006)
The frequent use of balance exercises aids in the protection of athletes from possible injuries. We suggest that coaches include sport-specific balance exercises into a daily soccer-training routine. We recommend the use of devices such as mini-trampolines and balance boards with the combination of certain soccer abilities to be more interesting to the players.